Cerai Tanpa Putusan Pengadilan Agama Dalam Islam dan Hukum Positif - Miftahul Jannah (Faculty of Sharia and Law UNISNU Jepara, 2021)
This study examines underhanded divorce, namely divorce that is carried out by someone without going through legal channels or without a divorce process in the Religious Courts. Whereas in the law it is clear that divorce can only be done before the court.From the description above, problems arise: First, what is the status of divorce without a decision by the Religious Courts. Second, how is the marital status of those who do not have a divorce certificate. Third, how important is the divorce certificate for divorce actors. To solve these problems, a library research method is used where the data are taken from existing books related to the titles that have been taken by the author to find answers to existing problems.The results of the study indicate that divorce without a court decision is not valid, in accordance with article 39 paragraph 1 of Law no. 1 of 1974 concerning marriage that divorce can only be carried out before a court session after the court concerned has tried and failed to reconcile the two parties. Therefore, people who divorce without a court decision are not valid but are legal according to religion only. Meanwhile, marriage without a divorce certificate is also invalid because the divorce certificate is authentic evidence as well as the marriage certificate. The divorce certificate is proof that the person has completed the divorce. 1 of 1974 that a marriage can be annulled if it does not meet the requirements to marry. So important is the divorce certificate to carry out a marriage, which is no less important, namely to ensure the management of child support rights from husband and wife, Gono Gini assets and marriage.AbstrakPenelitian ini mengkaji tentang Perceraian di bawah tangan yaitu perceraian yang dilakukan oleh seseorang dengan tidak melalui jalur hukum atau tanpa proses perceraian di Pengadilan Agama. Padahal dalam Undang- Undang sudah jelas bahwa perceraian itu hanya dapat dilakukan didepan pengadilan.Dari uraian di atas timbul masalah: Pertama, bagaimana status perceraian tanpa putusan Pengadilan Agama. Kedua, bagaimana status perkawinan yang tidak mempunyai akta cerai.Ketiga,sejauh mana pentingnya akta cerai bagi pelaku perceraian. Untuk menyelesaikan permasalahan tersebut, digunakan metode penelitian studi pustaka (Library Risearch) dimana data-data yang diambil dari buku yang ada yang berhubungan dengan judul yang telah ambil oleh penulis untuk mencari jawaban atas masalah yang ada.Hasil penelitian menunjukkan bahwa cerai tanpa putusan pengadilan itu tidak sah, sesuai dengan pasal 39 ayat 1 UU No. 1 tahun 1974 tentang perkawinan bahwa perceraian hanya dapat dilakukan didepan sidang pengadilan setelah pengadilan yang bersangkutan berusaha dan tidak berhasil mendamaikan kedua belah pihak. Orang yang bercerai tanpa putusan pengadilan tidak sah secara hukum positif tapi sah menurut agama saja. Akta cerai merupakan bukti bahwa orang tersebut sudah selesai melakukan perceraian, apabila sudah melakukan perkawinan maka harus dibatalkan sesuai dengan pasal 22 UU No. 1 tahun 1974 bahwa pernikahan dapat dibatalkan apabila tidak memenuhi syarat untuk melangsungkan perkawinan karena berkaitan dengan terjaminnya pengurusan hak tunjangan anak dari suami istri harta gono gini dan perkawinan.